Bridging Education for Sustainable Development and Climate Change Education in Africa: A Bibliometric Analysis of Research Trends, Gaps, and Emerging Frontiers - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2026)
Climate change poses an existential threat to Africa, yet the continent’s education systems remain under resourced to deliver effective Education for Sustainable Development (ESD) and Climate Change Education (CCE). No comprehensive mapping of ESD–CCE research in Africa exists. This study provides the first continent wide bibliometric analysis of ESD–CCE research in Africa (2015–2025), mapping publication trends, geographic and institutional productivity, collaboration networks, dominant and emerging themes, and research gaps. A systematic search of the Scopus database retrieved 312 peer reviewed documents. Bibliometric analysis was performed using Bibliometrix (R) and VOSviewer, including descriptive statistics, co authorship network analysis, keyword co occurrence mapping, and thematic evolution over two time periods (2015–2020; 2021–2025). Publications grew from 4 in 2015 to 90 in 2025, accelerating sharply after 2020. Research is highly concentrated: South Africa (33.3%), Nigeria (19.9%), and Kenya (12.2%) produce two thirds of output. Intra African collaboration is extremely weak (5.8% of documents). Dominant themes are sustainability, climate adaptation, and teacher training and curriculum integration. Emerging frontiers (transformative learning, indigenous knowledge) appear but remain underoperationalized. Eco anxiety is almost absent from the literature (3 documents), despite high climate vulnerability. Conclusion: African ESD–CCE research is growing but remains geographically skewed, poorly connected regionally, and neglects critical frontiers such as eco-anxiety, early childhood education, and longitudinal impact studies. We recommend establishing an African ESD–CCE research observatory, integrating indigenous knowledge into transformative learning frameworks, and developing validated instruments to measure eco anxiety in African youth.